(untitled) (Journal of Society of Surgeons of Nepal, 2025)
Introduction: Liver transplantation (LT) is the definitive treatment for End-Stage Liver Disease (ESLD), yet significant barriers prevent eligible patients from undergoing the procedure in low- and middle- income countries like Nepal. This study aimed to analyze the demographic and clinical characteristics of patients evaluated for liver transplantation, identify reasons for non- transplantation, and assess factors associated with these outcomes. Methods: A descriptive cross-sectional study included 70 patients evaluated for living donor LT at KIST Medical College Teaching Hospital, Lalitpur, a tertiary care center with an established liver transplant program. Data collected covered demographics, clinical details, and transplant eligibility, including MELD scores, reasons for non-transplantation, and outcomes. Results: The mean patient age was 52.2 ± 10.4 years, with a total of 55 (78.6%) being male. The mean MELD score at evaluation was 20.8±6.3. The primary reasons for not proceeding with transplantation were- unavailability of a suitable donor [66 (94.2%)], followed by financial constraints [47( 67.1%)]. Conclusion: This study highlights that many patients evaluated for liver transplantation could not undergo the procedure due to donor unavailability, financial constraints, and disease progression.